The Motives of Muhammadiyah Community Following the Majlis Dzikir of Al-Khidmah: (Case Study of Tarekat Community of al-Qadiriyyah wa al-Naqsyabandiyyah al-Utsmaniyyah) - Rosidi Rosidi; Abdulloh Hanif (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The Tarekat is an organized system of wirid, riyadah, and mujahadah under the direction of a mursyid (spiritual teacher) that promotes the pursuit of meaning and the deepening of religion as a means of perfection with an emphasis on the profound (esoteric components). With the emergence of the Majlis Dzikir of Al-Khidmah community-preserving assembly organization by Shaykh Ahmad Asrori al-Ishaqi, the tarekat al-Qadiriyyah wa al-Naqsyabandiyyah (TQN) al-Utsmaniyyah expanded quickly. This tarekat is followed by people from all backgrounds, including members of Muhammadiyah, through numerous inclusive variations. This study explores the motivations of the Muhammadiyah community and how they perceive TQN al-Utsmaniyyah. The instrument of analysis in this study is Max Weber’s Social Action Theory. It is a qualitative-descriptive study employing a phenomenological approach. The participants in this study were members of the Muhammadiyah community who were interested in taking part in the development of TQN al-Utsmaniyyah. The results showed that TQN al-Utsmaniyyah is regarded by Muhammadiyah people from two perspectives: first, the side of the tarekat that has inclusive qualities and various types of ease and ritual lightness, making the teachings of the tarekat seem more engaging and practical. Second, from the mursyid of TQN al-Utsmaniyyah’s part, Shaykh Ahmad Asrori al-Ishaqi, who is famous for being a charismatic individual who is kind, competent, and has a strong sense of community, The majlis dzikir of Al-Khidmah is followed by Muhammadiyah adherents for instrumental rational action factors and value-oriented acts, or decisions made by someone based on careful consideration and good or poor values.